GromaXy: uma ferramenta para integração do Galaxy com o GROMACS - Souza, Alfredo Guilherme da Silva (2017)
Considering the significant advances in biomolecular researches, the raise of various limitations is predicted. Thereby, reinforcing the link between science and technology, by introducing the new and effective development tools which can be used in a variety of scientific studies (i.e. Molecular Dynamics methods for drug discovery), becomes necessary. This method enables the realization of simulations in biomolecular studies in which atoms' behavior can be observed during a specific period of time. In the state of art various researches related to development of tools, whose main goal is facilitating Molecular Dynamics studies, are encountered. The GROMACS is one of these tools that is known as an open-source tool that has been used in lots of research projects. Due to the complexity of manipulating the GROMACS, the current study presents a new tool called GromaXy, which aims at providing a new interaction way with GROMACS, by introducing a new graphical interface which is much more convenient than the GROMACS command line. In addition to providing a new interaction way with GROMACS, the GromaXy also offers an adoptation of Atom Validation, which is another tool that has been developed in one of the previous studies. Atom Validation identifies the absent atoms in protein structure and show the to the user in form of a list. GromaXy was developed using a well-known framework in bioinformatic area called Galaxy. This framework was preferred due to its simple environment, the ability of sharing the work history and the history of realized experiments, enabling the high-level storage of data related to the trajectory of simulation process. The GromaXy was chosen as an adequate name which presents the join of Galaxy and GROMACS.